Fear, Growth, and Self-discovery: A Coming-of-Age Process in LUCY - Haze - Dimas Ramadhiansyah (Jurnal Komunikasi Global, 2024)
In the realm of music, especially within the K-pop genre, songs serve as dynamic mediums for addressing social issues. This research focuses on the `song "Haze" by LUCY. The selection of this song is emphasized due to its rich meanings capable of representing life, especially regarding individual journey from childhood to adulthood, resonating with universal themes of resilience, self-discovery, and social challenges in its lyrics. Additionally, "Haze" serves as a primary message about readiness for adulthood. This study utilizes semiotics, drawing from Charles S. Peirce's method, to uncover layers of meaning within the song's lyrics. Findings reveal a profound journey marked by fear, growth, and identity exploration. Through semiotic analysis, the study illuminates how individuals navigate internal struggles, overcome obstacles, and foster resilience. The lyrics capture emotional complexities, emphasizing the significance of self-identity and interpersonal relationships in navigating life's trials. Ultimately, maturity is depicted as the embrace of authenticity and inner strength amidst uncertainty.Di ranah musik, khususnya dalam genre K-pop, lagu-lagu berfungsi sebagai media dinamis untuk mengatasi isu-isu sosial. Penelitian ini berfokus pada lagu "Haze" oleh LUCY. Pemilihan lagu ini dalam penelitian ditekankan karena lagu ini kaya akan makna yang mampu merepresentasikan kehidupan, terutama tentang penggambarannya pada perjalanan individu dari masa kanak-kanak menuju dewasa, yang beresonansi dengan tema-tema universal tentang ketahanan, penemuan diri, dan tantangan-tantangan sosial dalam liriknya. Selain itu, "Haze" dapat dijadikan sebuah pesan utama tentang kesiapan diri menuju kedewasaan. Penelitian ini menggunakan semiotika, mengambil metode dari Charles S. Peirce, untuk mengungkap lapisan lapisan makna dalam lirik lagu tersebut. Temuan menunjukkan perjalanan yang mendalam yang ditandai dengan ketakutan, pertumbuhan, dan eksplorasi identitas. Melalui analisis semiotik, penelitian ini menemukan bagaimana individu menghadapi perjuangan internal, mengatasi rintangan, dan membangun ketahanan. Lirik-lirik tersebut menangkap kompleksitas emosional, menekankan pentingnya identitas diri dan hubungan interpersonal dalam menghadapi ujian kehidupan. Pada akhirnya, kedewasaan digambarkan sebagai pelukan atas keaslian dan kekuatan batin di tengah ketidakpastian.